Comparison of numerical simulation of finite and infinite square cylinder at high Reynolds number - Cheong, Wai Yang (2016)
Comparison of numerical simulation of square cylinders of finite and infinite height in a cantilever position is numerically simulated using large eddy simulation (LES). The infinite cylinder is defined as cylinder with no free end (mounted together with the base and top of the boundary). The height-to-diameter ratio (z/D) for the finite cylinder is 2 and 10 for the infinite case. The Reynolds number of 15000 for both cases was based on the cylinder diameter and free stream velocity. The tip effects from the free end of the finite cylinder and the base effects from the base of the finite cylinder show characteristics of strong three-dimensional wake. Regular vortex shedding in the infinite cylinder was found in the wake of the flow as was expected. For the finite case, irregular vortex shedding was observed, which was contributed by the strong flow over the free end of the cylinder. interesting observations such as a burst of vortex was observed at time, t=0.75s for the infinite case. Also, there are 3 high frequency peaks looking at the drag coefficients for the finite case. Pressure distributions, lift, drag and Strouhal numbers were also computed and discussed.